Relevant approaches to modernization of academic and material and technical process support of academic process in the field of knowledge “Health care” in terms of adapting to international assessment criteria - Pertseva, T O; Shponka, I S; Tverdokhlib, I V; O Yu Pototskaya (Medychni perspektyvy, 2019)
One of the important tasks in modernization of Ukrainian medical education is to bring it in line with international assessment criteria, which has become especially relevant after the introduction of the International Basic Medicine Examination in 2018. The aim of this work was to identify the most significant differences between international medical exams (for example, The United States Medical Licensing Examination, USMLE) and the national system of licensed exams KROK, and based on this, determine the direction of modernization of Ukrainian medical education for its adequate adaptation to new systems of assessment. The most significant differences between the two exams are: format (on computers / on paper); presence / absence of digital files with images and audio data in tasks; thematic focus of tests within one / several subjects; different list of items by which tasks are distributed; in the case of USMLE, there is a much higher motivation to pass the exam with the highest possible result. To adapt the medical education system to such features, it is necessary: to provide students with high-quality illustrated textbooks and meaningful digital data bases for each specialized subject; to actively use images (audio, video files) from these sources during the analysis of the material and all types of control (including test ones); to establish cooperation between the fundamental and clinical departments in the process of creating test tasks, as well as the exchange of digital materials for practical classes. Of particular importance is the synchronization of methodological approaches to conducting practical classes and assessment criteria not only in theoretical but also in clinical departments, which will make the learning process more transparent and understandable. Such a set of measures will help not only to adapt students to exams at the international level, but also will increase their interest and improve the effectiveness of the educational process. The employment of digital images, audio, video files will also contribute to the adequate preparation of students for new directions in medicine, such as telemedicine and telepathology.